Thermodynamics and kinetic studies of methyl orange dye adsorption in magnetic material-silica-zeolite (MM-Sio2-NZ) composite - Alrum Armid; Fahmiati Fahmiati; Halimahtussaddiyah Ritonga; Darwin Ismail; La Ode Ahmad Nur Ramadhan (The University of Mataram, 2023)
Using methyl orange (MO) in dye industries can cause the accumulation of MO waste in aquatic systems, including seawater. A magnetic material-silica-zeolite (MM-SiO2-NZ) composite was investigated in vitro to adsorb methyl orange (MO) dye. MM-SiO2-NZ composite was characterized using FTIR, XRF, and VSM. Adsorption studies with pH, concentration, contact time, and temperature variations were carried out to determine the adsorption capacity. The MM-SiO2-NZ characterization results by FTIR showed the presence of OH groups from Fe-OH, Si-OH, and Al-OH, and there were Fe-O, Si-O, Al-O, Si-O-Si, and Si-O-Fe groups. The results of XRF characterization showed that the metal oxide content of Fe2O3 in magnetic material (MM) was 75.39% and decreased to 52.63% after the MM-SiO2-NZ composite was formed. The characterization using VSM indicated the magnetic properties of MM to be 44.083 emu/g, then decreased to 11.407 emu/g after being composited. The adsorption of MM-SiO2-NZ tends to follow the Langmuir adsorption isotherm with a Langmuir constant (KL) value of 1.332 L/mg. Furthermore, the adsorption kinetics followed the pseudo-second-order kinetics with a constant value (k2) of 3×10-2 g.mg/min. MO dye adsorption by MM-SiO2-NZ took place spontaneously with Gibbs free energy (ΔG), enthalpy (ΔH), and entropy (ΔS) values of -1.109 kJ/mol, -38.687 kJ/mol, and -12.402 kJ/mol, respectively.